2015
DOI: 10.1177/1077801215589380
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Assault Perpetrators’ Justifications for Their Actions

Abstract: Perpetrators use rape supportive attitudes and sexual assault incident characteristics to justify forcing sex on their victims. Perpetrators who can justify their behaviors are at increased risk for future perpetration. This study examined the relationships between rape supportive attitudes, sexual assault incident characteristics, and the post-assault justifications of 183 men sampled from the community who self-reported committing at least one act of sexual aggression. Hierarchical multiple regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 69 publications
(125 reference statements)
2
28
0
1
Order By: Relevance
“…Sexual violence incidents were significantly more likely than other types of violence incidents to have occurred on campus than off campus, with someone known (i.e., an acquaintance, peer, or colleague) being the most frequently reported perpetrator, again similar to most comparable studies (Abbey et al, 2001; Wegner et al, 2015). However, the 14.6% of the students who were sexually victimized by a current or former intimate partner is an important segment not frequently reported or considered separately with different dynamics and different prevention strategies than those victimized by acquaintances or strangers.…”
Section: Discussionsupporting
confidence: 64%
“…Sexual violence incidents were significantly more likely than other types of violence incidents to have occurred on campus than off campus, with someone known (i.e., an acquaintance, peer, or colleague) being the most frequently reported perpetrator, again similar to most comparable studies (Abbey et al, 2001; Wegner et al, 2015). However, the 14.6% of the students who were sexually victimized by a current or former intimate partner is an important segment not frequently reported or considered separately with different dynamics and different prevention strategies than those victimized by acquaintances or strangers.…”
Section: Discussionsupporting
confidence: 64%
“…These findings demonstrate that this simulation produced the “in the moment” affect and cognitions that appear to motivate sexual aggression among men predisposed to act this way. Additionally the negative correlation between refusals and the perception that participants acted in ways that would be approved of by others, shows that perpetrators have some awareness that their behavior is not mere seduction or gentle persuasion (Ward et al, 1997; Wegner et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The fifth goal was to demonstrate that participants’ self-reported feelings and thoughts during the simulation were similar to those reported by perpetrators as justifications for their behavior in survey research and found to mediate sexual aggression proclivity in experimental research (Bouffard & Miller, 2014; Davis et al, 2012; Norris et al, 2002; Ward, Hudson, Johnston, & Marshall, 1997; Wegner, Abbey, Pierce, Pegram, & Woerner, 2015). The fifth hypothesis is that the number of refusals that participants received would be positively associated with (1) feeling immersed in the simulation, (2) feeling sexually aroused, (3) being mad at the woman for refusing them, and (4) thinking that she was playing hard to get and was leading them on.…”
Section: Goals Of the Current Studymentioning
confidence: 99%
“…Lalumière et al (2005) suggest that when comparing incarcerated rapists to non-sex offenders (e.g., violent offenders), however, many of these differences are reduced or are no longer statistically significant, suggesting there are important differences between offenders more generally and non-offenders. Thus, it is important to examine the relationship 12 As noted above, to the best of my knowledge, the following are the only studies that examine predictors of rape using a community sample (15 studies; 9 independent samples): Abbey et al, 2006;Abbey et al, 2007;Abbey, Jacques-Tiura, & LeBreton, 2011;Abbey et al, 2012;Calhoun et al, 1997;Cue Davis et al, 2014;Greene & Cue Davis, 2011;Jacques-Tiura et al, 2015;Knight & Sims-Knight, 2003;Lim & Howard, 1998;Senn et al, 2000;Wegner et al, 2015;. As well, some of these studies use the same sample of participants (Abbey et al, [2006 between potential causal factors of sexual aggression and sexually aggressive behaviour in both community and incarcerated samples of participants.…”
Section: Samples Of Sexually Aggressive Menmentioning
confidence: 99%
“…Online research, particularly the use of online panels, is one promising method of 1 To the best of my knowledge, the following are the only studies that examine predictors of rape (not rape-supportive cognition specifically) using a community sample (15 studies; 9 independent samples): Abbey, Parkhill, BeShears, Clinton-Sherrod, & Zawacki, 2006;Abbey, Parkhill, Clinton-Sherrod, & Zawacki, 2007;Abbey, Jacques-Tiura, & LeBreton, 2011;Abbey, Wegner, Pierce, & Jacques-Tiura, 2012;Calhoun, Bernat, Clum, & Fame, 1997;Cue Davis et al, 2014;Greene & Cue Davis, 2011; Jacques-Tiura, Knight & Sims-Knight, 2003;Lim & Howard, 1998;Senn, Desmarais, Verberg, & Wood, 2000;Widman, Olson, & Bolen, 2012. As well, some of these studies use the same sample of participants (Abbey et al, [2006], and Abbey et al [2007] shared a sample; Abbey, Jacques-Tiura, & LeBreton, [2011], , Abbey et al, [2012], Jacques-Tiura et al [2015], and Wegner et al [2015] shared a sample; and Widman, Olson, & Bolen [2012] shared a community sample).…”
mentioning
confidence: 99%